Reentry Attitude Control of Reusable Launch Vehicle Based on Event-Triggered Sliding Mode Control - Wen, Baoyu; Huang, Jiangshuai; Tan, Yaoyao; Gao, Tingting (2021 IEEE International Conference on Electronic Technology, Communication and Information (ICETCI), 2021)
In order to deal with unknown external disturbances in the reentry phase and save communication resource. In this paper, an event-triggered scheme based on sliding mode control is designed for the attitude regulation of a class of Reusable Launch Vehicle in reentry phase subject to unknown external disturbances. A sliding control mode based on event-triggered is designed and based on which the attitude control design of Reusable Launch Vehicle in reentry phase is proposed using backstepping technique. The stability analysis is given via Lyapunov function technique. Finally, the effectiveness of developed control scheme is validated through simulations.